KONTIBUSI PENDIDIKAN lIFE SKILL TERHADAP KARAKTER WIRAUSAHA PADA IBU RUMAH TANGGA DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN PEKANBARU - helmi, Thessa Krismania; Ayub, Daeng; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Benefits of this research To find out and analyze life skills education for housewives in Simpang Baru Village, Tampan District, Pekanbaru, To find out and analyze the entrepreneurial character of housewives in Simpang Baru Village, Tampan District, Pekanbaru. To find out and analyze the relationship between life skill education and entrepreneurial characteristics of housewives in Simpang Baru Village, Tampan District, Pekanbaru, to find out and analyze the contribution of life skill education to entrepreneurial character in housewives in Simpang Baru Village, Tampan District, Pekanbaru. This research is descriptive with a quantitative approach. The population in this study was 100 people. Sampling in this study uses simple random sampling in which the number of samples is 73 housewives. The instrument used was a questionnaire. Life Skill Education consists of 39 statements while Entrepreneurial Character consists of 37 statements. Life Skill Education Contribution to the Character of Entrepreneurship in Housewives in Simpang Baru Village, Tampan District, Pekanbaru City is measured by indicators of Life Skill Education for Self and Business Development, Various Life Skills, Interaction with Experts, Assessments, Establishing Business. Whereas the Character of Entrepreneurship with indicators of Confidence, Task-oriented and results, Risk taking, leadership, originality, oriented to, the future, honest and diligent. Life Skill Education for Housewives in Simpang Baru Village, Tampan District, Pekanbaru City is 4.29 with a high interpretation. Obtained the level of Entrepreneurship Character for Housewives in Simpang Baru Village, Tampan District, Pekanbaru City, 4.45 with a high interpretation. Then obtained Lifeskill Education contribution to the character of entrepreneurship in housewives is low that is equal to 29.90% meaning that there are still 71.10% determined by other factors that are not part of this study.Key Words: Life Skill Education, entrepreneurial character, housewife